Penerapan Gaya Arsitektur Industrial Tropis Pada Fasad Perumahan Austinville - Dian Lutfi Mahendra; Ar. Iwan Wibisono, ST., MT. IAI (Jurnal Mahasiswa Departemen Arsitektur, 2024)
The need for shelter is one of the basic needs for every human being. The most commonly used residence is the house. The need for housing is still an unresolved problem for the Indonesian government until 2022. Malang City is also not free from this impact, seen from its fairly dense population and the large number of visitors from various regions. The aspect of the house that is considered is the facade of the house in the Austinville housing complex. The facade is assessed from the level of application of the style applied to the housing, namely the tropical industrial architectural style. The method used in this research uses mixed methods through observation, interviews and distribution of questionnaires to residents. The variables used are facade elements consisting of roofs, walls, doors and windows as well as visual elements used for assessment. Observations show that the facade has adopted a tropical industrial style, but does not display all the characteristics of industrial or tropical architectural styles. For the questionnaire, respondents responded that the application of the style was 'appropriate' as seen from a five-point Likert scale from 'very unsuitable' to 'very suitable'. Keywords: application, façade, tropical industrial architectural style